Analysis The Determinants Of Going Concern Audit Opinion - Listi, Risma Kumara; Amirya, Mirna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The company's financial performance affects the provision of going concern audit opinion. Opinions related to business continuity given by auditors to companies are one of the bases for decision making for stakeholders. This study seeks to determine the effect of profitability, leverage, prior audited opinion, company size, and audit quality on the provision of going concern audit opinion. This study uses logistic regression analysis method. In accordance with the research criteria, the sample in this study amounted to 152 samples. The research object in this study is non-primary consumption companies, clothing and tourism sub-sectors listed on the Indonesia Stock Exchange for the period 2020-2023. This study found that profitability and prior audited opinion have a positive effect on going concern audit opinion. Meanwhile, leverage, company size, and audit quality have no significant effect on going concern audit opinion.